“Nonnative? Next!” Native-speakerism in world language job advertisements - Thompson, Amy S.; Asanov, Emil (Studies in Second Language Learning and Teaching, 2024)
Given the lack of research into native-speakerism among teachers of languages other than English (LOTEs), this qualitative study aims to bridge the gap by investigating the discriminatory and inclusive language employed in online recruitment for post-secondary institution instructors of LOTEs. The study also looks at how post-secondary institutions phrase language requirements and whether there is a difference in “native-speaker-teacher” bias depending on the language. For the purposes of this study, qualitative content analysis was used to examine 187 online job advertisements for teaching positions of different LOTEs that were posted by different post-secondary institutions across the United States. The findings of the study show that post-secondary institutions use discriminatory language such as “native” or “near-native” much more often than inclusive language such as “superior language skills,” regardless of the language(s) that the position advertises for. The findings, however, show that job candidates for teaching positions of LOTEs are often required to have “native” or “near-native” proficiency in at least two languages, most commonly English plus the target language of focus.